(untitled) (Clinics, 2014)
OBJECTIVES: This study aims to compare the prevalence of osteoarthritis in two groups: one comprising former professional soccer players and the other comprising non-professional-athlete participants. METHODS: Twenty-seven male former professional soccer players and 30 male volunteers from different non-sports professional areas participated in the study. All participants underwent bilateral knee radiography and magnetic resonance imaging. In addition, the quality of life, knee pain and joint function were evaluated and compared using questionnaires given to all participants in both groups. Specific knee evaluations, with regard to osteoarthritis and quality of life, were performed in both groups using the Knee Injury and Osteoarthritis Outcome Score subjective questionnaires and the Short-form 36. The chi-squared test, Fisher's exact test, the Mann-Whitney U test and Student's t-test were used for group comparisons. RESULTS: The between-groups comparison revealed significant differences in the following: pain, symptoms and quality of life related to the knee in the Knee Injury and Osteoarthritis Outcome Score subscales; the physical aspects subscale of the SF-36; total whole-organ magnetic resonance imaging scores with regard to the dominant and non-dominant knees. Former soccer players had worse scores than the controls in all comparisons. CONCLUSIONS: Both the clinical and magnetic resonance evaluations and the group comparisons performed in this study revealed that former soccer players have a worse quality of life than that of a control group with regard to physical aspects related to the knee; these aspects include greater pain, increased symptoms and substantial changes in radiographic and magnetic resonance images of the knee.